2021
DOI: 10.3389/fonc.2021.654185
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GINS4 Is Associated With Tumor Progression and Poor Survival in Hepatocellular Carcinoma

Abstract: PurposeOur research was aimed to identify the expression, clinical value and biological significance of GINS complex subunit 4 (GINS4) in hepatocellular carcinoma (HCC).Materials and MethodsGINS4 was initially screened through weighted gene co-expression network analysis (WGCNA). The TCGA, GEO, and TIMER databases were applied for analyzing the GINS4 mRNA expression in HCC. GINS4 protein levels were detected via immunohistochemistry (IHC). Receiver operating characteristic (ROC) curve was applied for estimatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Zhu et al found that GINS4 was highly expressed in gastric cancer and correlated closely with gastric cancer clinicopathological features such as OS and disease-free survival (DFS) [ 31 ]. Similar results were also found in colorectal cancer [ 32 ], pancreatic cancer [ 33 ] and hepatocellular carcinoma [ 34 ] and breast cancer [ 35 ].…”
Section: Discussionsupporting
confidence: 78%
“…Zhu et al found that GINS4 was highly expressed in gastric cancer and correlated closely with gastric cancer clinicopathological features such as OS and disease-free survival (DFS) [ 31 ]. Similar results were also found in colorectal cancer [ 32 ], pancreatic cancer [ 33 ] and hepatocellular carcinoma [ 34 ] and breast cancer [ 35 ].…”
Section: Discussionsupporting
confidence: 78%
“…Accordingly, we conducted our study using bioinformatics analysis. Previous study has reported the functional role of several GINS member in sarcoma [23][24][25]. This study used a bioinformatics approach to investigate the expression of the GINS family in sarcoma and its impact on the prognosis of sarcoma patients, and to further investigate the relationship with immune cell infiltration in the sarcoma microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, high expression of GINS1 promotes drug resistance in leukemia cells (Hsieh et al 2020) and help predicts clinical outcomes of colorectal cancer patients (Bu et al 2020b). On the other hand, high GINS4 results in tumorigenesis of human bladder cancer, colorectal cancer, and hepatocellular carcinoma (Yamane et al 2016;Rong et al 2020;Zhang et al 2021). However, our knowledge regarding the role of GINS2 in gastric cancer is limited.…”
Section: Discussionmentioning
confidence: 99%
“…BALB/c nude mice at 4 weeks old were selected for in vivo xenograft assay. Briefly, 5 × 10 5 stable-transfected KATO-III or MKN45 cells were subcutaneously injected into the mice (Chen et al 2021). After five days, the tumor diameter was measured by a vernier caliper every 5-days for one month, and the tumor volume was calculated according to the following formula: Volume = (π × length × width 2 )/6.…”
Section: In Vivo Studiesmentioning
confidence: 99%